Implementation of Six Sigma Method to Maintain The Quality of Construction Projects - Latief, Yusuf; Utami, Retyaning Puji (Makara Journal of Technology, 2009)
Implementation of Six Sigma Method to Maintain The Quality of Construction Projects. Six sigma (6-sigma) is a method that widely developed in the world, especially in manufacturing industry to decrease failures in achieving good quality in construction projects. The objective of this research is to explore the existing condition of quality management and the aplication of 6-sigma method in maintaining quality of construction projects. Structured interviews to experienced experts and people who were recommended by their companies were conducted. Non-parametric analysis using frequencies distribution procedures were used for analysis. The result shows that existing condition in quality management of construction project in Indonesia have been implemented 6-sigma method approach, that concern with is how to adapt with either from internal or external condition of that project.